![image](https://tex.z-dn.net/?f=+%5Cfrac%7B2%5Ccos2a-%5Csin4a%7D%7B2%5Ccos2a%2B%5Csin4a%7D+%3D%5Cfrac%7B-2cosa%2A%5Csina-1%7D%7B2cosa%2Asina%2B1%7D%3D%5C%5C%0A%5Cfrac%7B1%7D%7B%5Csin2a%2B1%7D-%5Cfrac%7B%5Csin2a%7D%7B%5Csin2a%2B1%7D%3B+%5C%5C%0Atg%5E2%28%7B+%5Cfrac%7B+%5Cpi+%7D%7B4%7D-a%7D%29%3D%5Cfrac%7B-2cosa%2Asina-1%7D%7B2cosa%2Asina%2B1%7D%3D+%5C%5C%0A%5Cfrac%7B1%7D%7B%5Csin2a%2B1%7D-%5Cfrac%7B%5Csin2a%7D%7B%5Csin2a%2B1%7D%3B+%5C%5C%0A%5Cfrac%7B1%7D%7B%5Csin2a%2B1%7D-%5Cfrac%7B%5Csin2a%7D%7B%5Csin2a%2B1%7D%3D%5Cfrac%7B1%7D%7B%5Csin2a%2B1%7D-%5Cfrac%7B%5Csin2a%7D%7B%5Csin2a%2B1%7D+%3D%3E%3B+%5C%5C%0A+%5Cfrac%7B2%5Ccos2a-%5Csin4a%7D%7B2%5Ccos2a%2B%5Csin4a%7D%3Dtg%5E2%28%7B+%5Cfrac%7B+%5Cpi+%7D%7B4%7D-a%7D%29%3B+%5C%5C%0A)
; \\
\frac{2\cos2a-\sin4a}{2\cos2a+\sin4a}=tg^2({ \frac{ \pi }{4}-a}); \\
" alt=" \frac{2\cos2a-\sin4a}{2\cos2a+\sin4a} =\frac{-2cosa*\sina-1}{2cosa*sina+1}=\\
\frac{1}{\sin2a+1}-\frac{\sin2a}{\sin2a+1}; \\
tg^2({ \frac{ \pi }{4}-a})=\frac{-2cosa*sina-1}{2cosa*sina+1}= \\
\frac{1}{\sin2a+1}-\frac{\sin2a}{\sin2a+1}; \\
\frac{1}{\sin2a+1}-\frac{\sin2a}{\sin2a+1}=\frac{1}{\sin2a+1}-\frac{\sin2a}{\sin2a+1} =>; \\
\frac{2\cos2a-\sin4a}{2\cos2a+\sin4a}=tg^2({ \frac{ \pi }{4}-a}); \\
" align="absmiddle" class="latex-formula">